Pengembangan Media Pembelajaran Berbasis Powerpoint Interaktif pada Materi Peredaran Darah Kelas V SDN Rejosari - Lailia Ulfa; Drajat Friansyah; Tri Juli Hajani (Journal of Elementary School (JOES), 2021)
This study aims to develop interactive powerpoint based learning media on blood circulation material for class V SDN Rejosari and determine the quality of interactive powerpoint-based learning media in terms of validity, practicality and potential effects of the developed media. The development model used in this study is a 4D model with the following steps: 1) Define; 2) Design; 3) Develop; 4) Desseminate. Based on the results of the validity tests conducted by linguists, material experts and media experts, they obtained an overall average score of 3,48 with Very Valid qualifications. The results obtained on the practicality aspect of the overall average of the small group test and field test of 3,47 with Very Practical qualifications, and the results obtained from the potential effect test obtained an average score which was converted into an overall percentage of 87,5% with High Effectiveness qualification. Keywords: Development, Powerpoint, Interactive, Blood Circulation